2017
DOI: 10.1213/ane.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ketamine Infusions for Neuropathic Pain Management: A Promising Therapy in Need of Optimization

Abstract: Intravenous ketamine infusions have been used extensively to treat often-intractable neuropathic pain conditions. Because there are many widely divergent ketamine infusion protocols described in the literature, the variation in these protocols presents a challenge for direct comparison of one protocol with another and in discerning an optimal protocol. Careful examination of the published literature suggests that ketamine infusions can be useful to treat neuropathic pain and that certain characteristics of ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(61 citation statements)
references
References 40 publications
1
53
0
7
Order By: Relevance
“…Mechanistically, spinal LTP involves presynaptic mechanisms as well as opening of T-type [voltagaegated Ca2 + channels type 3 (Ca v 3)] calcium channels and activation of NMDA receptors (Ikeda et al, 2003(Ikeda et al, , 2006Zhuo, 2016b). These receptors have long been implicated in the etiology of neuropathic pain (Woolf and Thompson, 1991;Kerr et al, 1999;Latremoliere and Woolf, 2009;Salter and Pitcher, 2012;Hildebrand et al, 2016), and this may account for the effectiveness of the NMDA receptor blocker, ketamine, in the management of chronic pain (Hewitt, 2000;Niesters et al, 2014;Maher et al, 2017) and the observation that T-type calcium channel blockers mibefradil and ethosuximide can reverse neuropathic pain in an animal model (Dogrul et al, 2003). Physiological blockade of NMDA channels with Mg 2+ has been shown to be effective in reducing signs of pain in animal models (Brill et al, 2002;Rondon et al, 2010), and there is some evidence that it may play a role in the treatment of human neuropathic pain (Pickering et al, 2011).…”
Section: E Other Spinal Mechanisms Of Central Sensitizationmentioning
confidence: 99%
“…Mechanistically, spinal LTP involves presynaptic mechanisms as well as opening of T-type [voltagaegated Ca2 + channels type 3 (Ca v 3)] calcium channels and activation of NMDA receptors (Ikeda et al, 2003(Ikeda et al, , 2006Zhuo, 2016b). These receptors have long been implicated in the etiology of neuropathic pain (Woolf and Thompson, 1991;Kerr et al, 1999;Latremoliere and Woolf, 2009;Salter and Pitcher, 2012;Hildebrand et al, 2016), and this may account for the effectiveness of the NMDA receptor blocker, ketamine, in the management of chronic pain (Hewitt, 2000;Niesters et al, 2014;Maher et al, 2017) and the observation that T-type calcium channel blockers mibefradil and ethosuximide can reverse neuropathic pain in an animal model (Dogrul et al, 2003). Physiological blockade of NMDA channels with Mg 2+ has been shown to be effective in reducing signs of pain in animal models (Brill et al, 2002;Rondon et al, 2010), and there is some evidence that it may play a role in the treatment of human neuropathic pain (Pickering et al, 2011).…”
Section: E Other Spinal Mechanisms Of Central Sensitizationmentioning
confidence: 99%
“…Ketamine's analgesic properties in acute pain likely derived from its reversible antagonism of NMDA receptor, although it exerts effects on pi -opioid, muscarinic, monoaminergic receptors, GABA receptors. Ketamine when administrated in sub-anesthetic doses prevents the development of central sensitization, hyperalgesia and opioid resistance [17] .…”
Section: Discussionmentioning
confidence: 99%
“…10,43 A Phase 2, randomized, double-blind, pilot study evaluating safety and pharmacological effects of elosulfase alfa in patients with Morquio A syndrome concluded that patients with relatively good endurance showed a trend of increased exercise capacity and muscle strength and decreased pain. 40 Other interventions for pain management in MPS patients may include infusions of lidocaine 40,44 or ketamine 45 for neuropathic pain and other chronic pain states, radiofrequency ablation, 46,47 particularly for hip pain, and peripheral nerve blocks. 48 Current exploratory options include pamidronate acid 49 and dexmedetomidine.…”
Section: Treatment Of Pain In Mpsmentioning
confidence: 99%